Introduction of an innovative day surgery pathway for unicompartmental knee replacement: no need for early knee flexion. Issue 1 (March 2019) - Jenkins, Cathy; Jackson, William; Bottomley, Nicholas; Price, Andrew; Murray, David; Barker, Karen
Abstract: Objectives: To evaluate the introduction of an innovative rehabilitation protocol, delaying knee flexion, for patients receiving unicompartmental knee replacement. Design: Longitudinal cohort. Setting: Specialist Orthopaedic Unit within an NHS Foundation Trust. Participants: 669 consecutive patients undergoing unicompartmental knee replacement. Intervention: An innovative rehabilitation protocol, delaying knee flexion. Main Outcome Measures: Length of stay, range of movement, Surgical Satisfaction Questionnaire. Results: There were 669 consecutive primary unilateral unicompartmental knee replacements from September 2016 to February 2018. In total 264 patients (39%) went home on the day of surgery, 253 (38%) on day 1 and 152 (23%) stayed in 2 or more days (range 2 to 28 days). The mean length of stay reduced from 2.6 to 1.2 days (median 1 day). Mean flexion was 110° (range 30 to 140) at 6 weeks. The surgical satisfaction questionnaire showed that 90% of patients discharged on day 0 were very satisfied with the results of surgery. Conclusion: Many components of traditional care were altered to introduce this protocol. The most important factors were delayed knee flexion providing benefits in terms of early mobilisation with no short term detriment, physiotherapists working late shifts, a consistent message and patient education. It was safe, effective and patient satisfaction was high.